The Use of Comics as a Tuberculosis Learning Medium for Junior High School Students - Utomo, Budi; Fatmaningrum, Widati; , Sulistiawati; Fauziyah, Shifa; Sucipto, Teguh Hari; Khuen, Chan Chow (Folia Medica Indonesiana, 2024)
Highlights: 1. Comics centered around tuberculosis offer a novel method tailored for specific audiences, specifically children or those of school age, to learn about the disease. 2. The tuberculosis comics feature the etiology, prevention, and treatment of tuberculosis conveyed through their unique design. 3. Comics can be an innovative promotional method to support the preventive campaign against tuberculosis. Abstract As a tropical country, Indonesia continues to grapple with the prevalence of tuberculosis. This study conducted by the Department of Public Health and Preventive Medicine at Universitas Airlangga, Surabaya, Indonesia, presented a novel approach to prevent tuberculosis through measures tailored to the socio-cultural context of the population. Specifically, this study assessed how effective the use of tuberculosis comics is as an educational tool to inform junior high school students about tuberculosis. This research was quasi-experimental, with a one-group pre-test-post-test design. Seventy junior high school students in Dukun District, Gresik, Indonesia participated in this study. Each participant received a questionnaire consisting of ten questions about tuberculosis. Afterward, tuberculosis education was shared through comics. The post-test was carried out using the same questions as the pre-test. The data were analyzed using the R Program for Windows, version 4.1.3 (Auckland University, New Zealand). The analysis revealed a significant difference between the pre-test and post-test results (p < 0.0001). As indicated by the data, comics proved to be an effective method of educating people about infectious diseases, specifically tuberculosis. Here, we introduce an educational tool designed to revitalize the educational method for disseminating knowledge about infectious diseases. Ultimately, comics can increase students' interest in learning about tuberculosis, including its etiology, prevention, and treatment strategies.